#
Please don't send the link.

$\mathbf{11}\mathbf{.}If2x={y}^{\frac{1}{5}}+{y}^{\frac{1}{5}}and\left({x}^{2}-1\right)\frac{{d}^{2}y}{d{x}^{2}}+\lambda x\frac{dy}{dx}+ky=0,then\lambda +kisequalto:\phantom{\rule{0ex}{0ex}}\left(1\right)-23\phantom{\rule{0ex}{0ex}}\left(2\right)-24\phantom{\rule{0ex}{0ex}}\left(3\right)26\phantom{\rule{0ex}{0ex}}\left(4\right)-26\phantom{\rule{0ex}{0ex}}$

Please check a question and correct right. you right 2x=y^(1/5)+y^(1/5) I think this not correct. Thanks

Regards

**
**